Identification of Financial Distress With Company Size As A Moderating Variables in Southeast Asia Property and Real Estate Industry - Deni Sunaryo (Publisher Cv. Inara, 2021)
This study aims to identify Financial Distress with Firm Size as a moderating variable in the property and real estate industry in Southeast Asia for the period 2012-2019. In identifying financial distress, the dimensions of Net Profit Magin, Current Ratio, and Debt To Asset Ratio are used. The sample used in this research is the company's complete financial statements from the 2014–2019 research year of 35 companies obtained by using purposive sampling technique. The data collection technique uses the documentation method, while the data analysis technique uses multiple linear regression analysis which is supported by the classical assumption test, namely the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test and model test moderation. The results showed that partially the Net Profit Margin, Current Ratio, Debt to Asset Ratio variables partially had a significant effect on Financial Distress, and Net Profit Margin, Current Ratio and Debt to Asset Ratio simultaneously had a significant effect on Financial Distress in the Property and Real Industry. Southeast Asia estate, whereas for the moderation model Firm size does not moderate Net Profit Margin, Current Ratio, Debt to Asset Ratio to Financial Distress. The value of R Square is 53.4%, indicating that the Financial Distress variable is influenced by all NPM, CR and DAR variables, the remaining 46.6% is influenced by other variables outside of this study including changes in exchange rates, differences in inflation, differences in interest rates, independence of the central bank. , economic growth, expectations, and so on. Recommendations for further research are to replace the moderating variables with other dimensions or indicators.